PENGEMBANGAN BAHAN AJAR BERBASIS PENDEKATAN DEEP LEARNING DALAM KEMAMPUAN MENGANALISIS TEKS BIOGRAFI KELAS X - Eka Nur Aminatus Sholihah; Laila Tri Lestari; Iib Marzuqi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Indonesian language instruction regarding biographical texts for Grade X students at MA Matholi’ul Anwar Simo faces challenges because the existing teaching materials fail to optimally develop students' abilities to analyze the structure, linguistic elements, exemplary values, and messages within such texts. Furthermore, the materials do not fully support the implementation of the *Kurikulum Merdeka* (Independent Curriculum), which emphasizes "Deep Learning." This study aims to describe the validity, efficiency, and effectiveness of Indonesian language teaching materials based on the Deep Learning approach, designed to enhance the biographical text analysis skills of Grade X students at MA Matholi’ul Anwar Simo. The study employs the Research and Development (R&D) method using the ADDIE model, comprising the stages of analysis, design, development, implementation, and evaluation. Research subjects included subject matter experts, design experts, an Indonesian language teacher, and Grade X students. Data were collected through observations and questionnaires assessing validity, efficiency, and effectiveness, and were subsequently analyzed using quantitative descriptive statistics (percentages). The results indicate that the teaching materials achieved validity scores of 94.8% from subject matter experts and 91.4% from design experts, placing them in the "highly valid" category. Efficiency, based on teacher assessment, reached 96%, falling into the "highly efficient" category. Regarding effectiveness, the materials achieved an average score of 91% ("highly effective") during the limited trial, while the field trial deemed them highly suitable for use. Consequently, the Deep Learning-based teaching materials are considered valid, efficient, and effective, making them suitable for Indonesian language instruction for Grade X students at MA Matholi’ul Anwar Simo.